USAHA MASYARAKAT MENCEGAH KEJAHATAN - Petrus Irwan Panjaitan (to-ra, 2018)
Abstract Prevention is better than overcoming, efforts to prevent crime by relying on the potential of the community is a big advantage for the creation of effectiveness and ef ciency of crime prevention and mitigation. The rise of crimes that occur in society is a social reality that cannot be denied, crimes not only worry the government also threatens the sense of security for every member of the community. Evil arises and develops in the midst of society, it is even a product of a heterogeneous society, because it is not possible to be destroyed but can only be prevented. Efforts to prevent crime can be done through a social approach by focusing on the role of individuals and members of the community, protecting yourself by not letting go, not providing stimulation will be effective in preventing crime. Keywords: Prevention of crime; mitigation; societ; security.